2016
DOI: 10.1590/2317-1782/20162015202
|View full text |Cite
|
Sign up to set email alerts
|

Influência da amostra de fala na classificação perceptiva da hipernasalidade

Abstract: RESUMO Objetivo Investigar a influência do tipo de amostra de fala, conversa espontânea ou repetição de sentenças, sobre o índice de concordância intra e interavaliadores obtido na classificação perceptiva da hipernasalidade. Métodos Foram selecionadas e editadas 120 amostras de fala gravadas em áudio (60 contendo trechos de conversa espontânea e 60 contendo repetição de sentenças) de indivíduos com fissura de palato±lábio reparada, de ambos os sexos, com idade entre 6 e 52 anos (média=21±10 anos). Três fono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
(54 reference statements)
0
7
0
3
Order By: Relevance
“…These results corroborate the literature that also reports reduced inter-raters agreement coefficients in studies that used the ordinal scale, as an assessment method. Studies performed in the Institution showed coefficients that vary from regular to moderate for several speech samples, including spontaneous conversation (10,22,23) , and in the international literature, moderate coefficients of inter-raters agreement were verified (26,27) . According to some authors, this is a worrying data regarding the speech assessment of individuals with cleft, bearing in mind the importance of the speech resonance as clinical decision guiding (28) .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These results corroborate the literature that also reports reduced inter-raters agreement coefficients in studies that used the ordinal scale, as an assessment method. Studies performed in the Institution showed coefficients that vary from regular to moderate for several speech samples, including spontaneous conversation (10,22,23) , and in the international literature, moderate coefficients of inter-raters agreement were verified (26,27) . According to some authors, this is a worrying data regarding the speech assessment of individuals with cleft, bearing in mind the importance of the speech resonance as clinical decision guiding (28) .…”
Section: Discussionmentioning
confidence: 88%
“…Historically, the ordinal scale is the most used for the hypernasality rating, both in researches and clinical practice (8)(9)(10) , because it is a more appropriate method for the clinical context. Additionally, the obtained ratings are relatively easy to be compared among different scales and listeners (9,11) .…”
Section: Introductionmentioning
confidence: 99%
“…Though subjective, perceptual assessment is considered the gold standard for evaluation of speech in individuals with cleft palate and the main indicator of clinical significance of this symptom (1,25,26) . One limitation of the present study is that the presence or absence of hypernasality was defined based on presential evaluation performed by a single examiner during routine follow-up of these patients, whose data were registered.…”
Section: Discussionmentioning
confidence: 99%
“…Tereza fez pastel. A árvore dá frutos e flores" (22) . The score of 27% wads considered to indicate the limit of normality (24) .…”
Section: Nasometryunclassified
“…The diagnosis of hypernasality is mainly achieved by auditory perceptual evaluation of speech, considered the "gold standard" to evaluate the symptoms related to VPD. However, due to its subjective nature the auditory perceptual evaluation is often associated with an instrumental evaluation to define the approach to be followed (1,21,22) .…”
Section: Introductionmentioning
confidence: 99%